Synthetic application of gold complexes on magnetic supports - Amirmahani, Najmeh; Rashidi, Mohsen; Mahmoodi, Nosrat O. (Applied organometallic chemistry, 2020)
Gold nanocatalysts (GNCs) have recently become a hot topic and are widely used in chemistry. Between heterogeneous and homogeneous catalyses, two main types of catalyses, heterogeneous catalysts have gained importance because of their ease of separation from the mixture with low contamination of the products. Currently, nano‐heterogeneous catalysis is the main subject in a wide range of research studies because nanostructures have unique abilities that are found only at the nano‐level of the molecular world. This review selectively discusses the magnetic phenomena of heterogeneous GNCs, in which their inherent magnetic property provides many advantages over the nonmagnetic counterparts and also highlights the synthesis, development, and recyclability of various types of magnetic GNCs in well‐known organic reactions. These insights are useful for researchers working on the future of magnetic‐type gold nanocatalysis to enhance organic transformations, in both rate and yield. The major attractions of magnetic AuNC are its high potential; genuine size; structure/activity dependence;being a support material able to stabilize itself; its economical application in industrial processes; excellent synergy with Ag, Cu, Zn, Pt, Pd, Ti, Co, Ni, Fe, etc; and its application in biorefinery reactions.